EGFR Signaling and its inhibition by EGFR inhibitors in NSCLC - Patel, Rajvi (International Journal of Applied Sciences and Biotechnology, 2014)
Lung cancer is the third most cancer among the population. The American society’s estimation for lung cancer in the United States for 2014 states that about 2,24,210 people are suffering from the lung cancer and 1,59,260 deaths are occur from lung cancer. Among all the types of lung cancer, NSCLC (Non-Small cell Lung Cancer) represents 85% of the lung cancer. The estimated spread of NSCLC is 2,26,160 and 1,60,340 cases are of death in 2012. One of the risk factor for NSCLC is over expression of epidermal growth factor receptor (EGFR) and its intracellular signaling pathways. EGFR is over expressed in 40-80 % cases of NSCLC. EGFR belongs to the ErbB family of receptor tyrosinekinases (RTK) having molecular weight 170 to 185 kDa. Epidermal Growth Factor (EGF) binds to the EGFR at its extracellular domain and this binding leads to the homo or hetero dimerization and autophosphorylation of EGFR which initiates the several intracellular pathways. Several mutations in EGFR or in any of the proteins of the pathway leads to the growth and survival of the tumor cells. So in order to inhibit the growth of tumor cell, several EGFR inhibitors and targeted therapies are found to target the particular mutations. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11263 Int J Appl Sci Biotechnol, Vol. 2(4): 375-388